2002
DOI: 10.1042/bj20020547
|View full text |Cite
|
Sign up to set email alerts
|

Topological analysis of peripherin/rds and abnormal glycosylation of the pathogenic Pro216→Leu mutation

Abstract: Peripherin/ rds is an integral membrane glycoprotein found in the rim regions of vertebrate photoreceptor cell discs. The protein is believed to be involved in both formation and maintenance of the characteristic flattened morphology of the outer segment discs and its essential nature is demonstrated by the wide range of retinal degenerative disorders in which the protein has an involvement. Little structural data has been determined for peripherin/ rds, but a topological model of the protein has been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…4) corresponding to apparent molecular weights of *37 and *40 kD being the dominant species. The apparent molecular weight of 37 kD is consistent with the apparent molecular weight of the monomer reported in the literature (Wrigley et al 2002). The same two bands are present upon analysis with Western blot at apparent molecular weights of *37 and *40 kD.…”
Section: P/rdsp Expression In Pichia Pastorissupporting
confidence: 75%
See 3 more Smart Citations
“…4) corresponding to apparent molecular weights of *37 and *40 kD being the dominant species. The apparent molecular weight of 37 kD is consistent with the apparent molecular weight of the monomer reported in the literature (Wrigley et al 2002). The same two bands are present upon analysis with Western blot at apparent molecular weights of *37 and *40 kD.…”
Section: P/rdsp Expression In Pichia Pastorissupporting
confidence: 75%
“…From previous studies it is known that an additional glycosylation site is created by this mutation (Wrigley et al 2002), and it was suggested that the attachment of two bulky carbohydrate chains to the protein may result in an altered conformation in the protein. The SDS-PAGE analysis presented here indicates that the glycosylation status of wild-type p/RDS and the P216L mutant expressed in S2 cells is the same; therefore, it is not possible to completely test this hypothesis.…”
Section: Implications Of the CD Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its N-and C-terminal domains are cytosolic, whereas its two extracellular loop domains (D1 and D2) project into the enclosed discs in rods and the extracellular space between lamellae in cones (24). The C-terminal domain is known to direct the targeting of RDS complexes to the OS, engage in protein-protein interactions, and form an amphipathic helix that is thought to play a role in maintaining the unique membrane topology of the OS itself by potentially regulating membrane fusion or curvature (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%